MRD response in relapsed/refractory FL after obinutuzumab plus bendamustine or bendamustine alone in the GADOLIN trial - Pott, Christiane; Sehn, Laurie H; Belada, David; Gribben, John; Hoster, Eva; Kahl, Brad; Kehden, Britta; Nicolas-Virelizier, Emmanuelle; Spielewoy, Nathalie; Fingerle-Rowson, Guenter; Harbron, Chris; Mundt, Kirsten; et al. (Leukemia, 2020)
We report assessment of minimal residual disease (MRD) status and its association with outcome in rituximab-refractory follicular lymphoma (FL) in the randomized GADOLIN trial (NCT01059630). Patients received obinutuzumab (G) plus bendamustine (Benda) induction followed by G maintenance, or Benda induction alone. Patients with a clonal marker (t[14;18] translocation and/or immunoglobulin heavy or light chain rearrangement) detected at study screening were assessed for MRD at mid-induction (MI), end of induction (EOI), and every 6-24 months post-EOI/discontinuation by real-time quantitative PCR. At MI, 41/52 (79%) patients receiving G-Benda were MRD-negative vs. 17/36 (47%) patients receiving Benda alone (p = 0.0029). At EOI, 54/63 (86%) patients receiving G-Benda were MRD-negative vs. 30/55 (55%) receiving Benda alone (p = 0.0002). MRD-negative patients at EOI had improved progression-free survival (HR, 0.33, 95% CI, 0.19-0.56, p < 0.0001) and overall survival (HR, 0.39, 95% CI, 0.19-0.78, p = 0.008) vs. MRD-positive patients, and maintained their MRD-negative status for longer if they received G maintenance than if they did not. These results suggest that the addition of G to Benda-based treatment during induction can significantly contribute to the speed and depth of response, and G maintenance in MRD-negative patients potentially delays lymphoma regrowth.
Keywords: Neoplasm, Residual; nehodgkinský lymfom; Humans; lidé středního věku; Bendamustine Hydrochloride; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; senioři; lidé; humanizované monoklonální protilátky; doba přežití bez progrese choroby; Lymphoma, Non-Hodgkin; Adult; bendamustin hydrochlorid; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; rituximab; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Lymphoma, Follicular; Aged, 80 and over; Rituximab; senioři nad 80 let; Progression-Free Survival; mužské pohlaví; folikulární lymfom; reziduální nádor